2021
DOI: 10.3390/agronomy11020268
|View full text |Cite
|
Sign up to set email alerts
|

Updated Characterization of Races of Plasmopara halstedii and Entomopathogenic Fungi as Endophytes of Sunflower Plants in Axenic Culture

Abstract: The management of downy mildew (Plasmopara halstedii) in sunflower, is heavily dependent on genetic resistance, whilst entomopathogenic fungi (EF) can reduce other sunflower diseases. In this work, we characterized P. halstedii from Spain and other countries collected in the past few years. Twenty-three races were identified (the most frequent in Spain being 310, 304, 705 and 715), with an increasing proportion of highly virulent races. Five isolates from countries other than Spain overcame the resistance in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…Genetic resistance of the sunflower to P. halstedii is provided by dominant resistance genes, named Pl genes, of which 36 (Pl 1 -Pl 35 , and Pl arg ) have been identified up to 2019 (Ma et al 2019). The search for new sources of resistance remains relevant because the pathogen has already overcome resistance genes: about 50 physiological races of P. halstedii have been registered worldwide (Viranyi et al 2015;Spring 2019;Gilley et al 2020;Miranda-Fuentes et al 2021) and 11 of them were known to occur in Russia until 2020 (Iwebor et al 2019). In this article, we report on an undescribed race 337, isolated from sunflower plants infected with downy mildew in 2020 in the southern part of the Russian Federation.…”
mentioning
confidence: 99%
“…Genetic resistance of the sunflower to P. halstedii is provided by dominant resistance genes, named Pl genes, of which 36 (Pl 1 -Pl 35 , and Pl arg ) have been identified up to 2019 (Ma et al 2019). The search for new sources of resistance remains relevant because the pathogen has already overcome resistance genes: about 50 physiological races of P. halstedii have been registered worldwide (Viranyi et al 2015;Spring 2019;Gilley et al 2020;Miranda-Fuentes et al 2021) and 11 of them were known to occur in Russia until 2020 (Iwebor et al 2019). In this article, we report on an undescribed race 337, isolated from sunflower plants infected with downy mildew in 2020 in the southern part of the Russian Federation.…”
mentioning
confidence: 99%
“…Earlier in Italy, Tosi and Zazzerini [ 32 ] and Tosi and Beccari [ 33 ], as well as Spring [ 18 ], published results about the spread of virulent pathotypes. More recently, Miranda-Fuentes et al [ 26 ] confirmed pathotypes 301 and 715 in Italian samples. We identified pathotype 717 for the first time in Italy.…”
Section: Discussionmentioning
confidence: 90%
“…Knowledge of the distribution of P. halstedii pathotypes is of utmost importance for effective pest management; however, there is only limited information about pathotype diversity for some vital sunflower-growing countries [ 18 , 21 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1992, P. halstedii has been subject to quarantine regulations in the European Union (directive 92/103/CEE), but in 2019 was removed from the list [ 11 ]. Since 2006, the number of P. halstedii races has increased from 35 [ 12 ] to 41 in 2014 [ 13 ] and 50 in 2018 [ 14 , 15 , 16 , 17 ]; the highest genetic diversity of the pathogen was reported in Canada, the USA, and France [ 18 ]. The disease was first detected in France in 1966 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%